Mizoram: an Insight - Kumar Das, Samares (International Journal of Bio-resource and Stress Management, 2023)
Mizoram, the abode of Mizo tribe, is one of the seven states (Seven Sisters) in north-east India. Until the beginning of twentieth century Mizos were living a primitive life completely isolated and unknown to the rest of the world. It is only after the British intervention that the Mizos became known to the outside world. Since then they have adopted Christianity as their religion. This paper provides a glimpse of Mizoram from historical, geographical, agro-ecological and socio-economic perspectives.